-x+8=-5x+0

Simple and best practice solution for -x+8=-5x+0 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -x+8=-5x+0 equation:


Simplifying
-1x + 8 = -5x + 0

Reorder the terms:
8 + -1x = -5x + 0

Reorder the terms:
8 + -1x = 0 + -5x
Remove the zero:
8 + -1x = -5x

Solving
8 + -1x = -5x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '5x' to each side of the equation.
8 + -1x + 5x = -5x + 5x

Combine like terms: -1x + 5x = 4x
8 + 4x = -5x + 5x

Combine like terms: -5x + 5x = 0
8 + 4x = 0

Add '-8' to each side of the equation.
8 + -8 + 4x = 0 + -8

Combine like terms: 8 + -8 = 0
0 + 4x = 0 + -8
4x = 0 + -8

Combine like terms: 0 + -8 = -8
4x = -8

Divide each side by '4'.
x = -2

Simplifying
x = -2

See similar equations:

| 3m-6+2m=4 | | 2.2x+47.7=9.3-10.6x | | 0.24y-0.8=0.14y+1-0.8y | | -5(y-3)=30 | | s+28-4s=5s-12 | | 10x^2-25x+60=0 | | 9y-24=-18+3y | | 3q+.5=2q-.125 | | M^2-7m+3=0 | | x-0.7=9.87 | | 4X+5=9X+3 | | -13m=39 | | .87x=64 | | y=-2(2x+9)+7 | | 2x+5=3x-3 | | .87x=56 | | 6(2m-7)= | | (8)(.16)(7)=8(.16)(7) | | y=-2x^2+12x-8 | | y=x^2-4x-3 | | y=3(6x+3)-5 | | -5[a+2]=2a+4 | | -9+2x=5x-30 | | x^4-16x^3+48x^2-144x-1312=0 | | 1+3x=-2x+31 | | 6c-3-2c=4c+4 | | 4x-32=4 | | 5x+7+3x=79 | | 29x^2-27x=0 | | 5r+5=15 | | 5(3-n)=5(3)-5n | | 10x=3x+-28 |

Equations solver categories